A NEED ASSESSMENT OF ETHICS COURSE FOR PRIMARY CARE PHYSICIAN: PHYSICIANS' PERSPECTIVE IN YOGYAKARTA PROVINCE, INDONESIA - Nurrokhmanti,, Hikmawati; Heru, Adi; Joseph, Hari Kusnanto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Primary care physicians, as first-line doctors, deal with ethical cases that challenge them to make the best patient decisions. Helping primary care physicians to be more aware of ethical cases and the process of case decision-making will improve all stakeholder's needs. Physician standard opinion on the best decision for their patient will be the baseline of suited training for them.Methods: We conducted a mixed-method study to understand GP decisions regarding certain ethical cases. In the quantitative phase, we used and presented several standardized ethical cases with several "decisive" options followed by reason. For qualitative, in-depth guided interview was done with several physicians. The data was analyzed by close system coding. Results: We gained 36 responses from several physicians with 12 in-depth interviews. In the quantitative, we found that two questions related to communicating the mistake and the rural problem had the worst response, showed by highly unfavourable answers. The interview found that most physicians find it hard to decide on ethical cases, acknowledge religion as one aspect for making the decision, and expect a clear guideline that will help them make a firm decision regarding "difficult" dilemma cases. Conclusion: To avoid bad decision-making in ethical-related cases, the physician must take another training since low awareness of ethical cases will lead to unfavourable decisions regarding some dilemmas. Considering the methods and number of subjects in this research, the training should apply a specific strategy to all physicians.